Obstacles and challenges of managing Sekar Teratai Buddhist Sunday School (SMB) in Jepara District - Darma, Widia; Hartono, Rudi; Mujahidin, Endin; Priyambada, Galih; Haiti, Diana (Technium Social Sciences Journal, 2021)
The purpose of this research is to describe in depth the obstacles and challenges in managing the management of the Sekar Teratai Buddhist Sunday School (SMB) management. This research will use a qualitative research approach. The data collection techniques of this research will use observation, interview and documentation study techniques. The research procedure used in this study consisted of several research steps with the Robert case study method. The results of this study are 1) The low capacity and capability of human resources in managing SMB, 2) The absence of financial independence, 3) The existence of Sunday schools is supported by high loyalty of teachers and parents, 4) Low support from foundations and assemblies in development and improvement Sunday School quality.